Synovial fluid-inspired biomimetic lubricating microspheres: Zwitterionic polyelectrolyte brushes-grafted microgels - Guoqiang Liu; Yang Feng; Xiaohua Gao; Zhuo Chen; Nan Zhao; Feng Zhou; Weimin Liu (Friction)
Abstract Synovial fluid is made up of various biomacromolecules, including hyaluronic acid, aggrecans, lubricins, and phosphatidylcholine lipid, which are assembled onto the surface of articular cartilage in a gel state. Among them, brush-like biomacromolecules or assemblies have a vital effect on human joint lubrication. Inspired by this, the combination of brush-like molecular structures and gel-like assembly may be an efficient approach for the synthesis of biomimetic lubricating matters. Learning from the lubrication system of human joints, poly(2-methacryloyloxyethyl phosphorylcholine) (PMPC) brushes grafted poly(N-isopropylacrylamide-co-acrylic acid) (poly(NIPAAm-co-AA)) microgels, abbreviated as MBs-g-MGs, were synthesized as one kind of biomimetic lubricating additives. It is worth noting that this bionic strategy considered both molecular structure and assembled form, which enabled this hairy microgel to achieve low friction in aqueous medium. Meanwhile, the effective lubrication was still achieved when using MBs-g-MGs at high temperature, indicating that this microgel maintains a good lubricating effect over a wide range of temperature. In addition, this kind of microgel possessed good biocompatibility, which laid the foundation for potential biomedical applications. Looking beyond, these biomimetic microgels may provide an effective lubricating effect for water-based sliding interfaces, especially in biomedical systems.